Edwardsiella tarda Bacteremia. A Rare but Fatal Water- and Foodborne Infection: Review of the Literature and Clinical Cases from a Single Centre - Yuji Hirai; Sayaka Asahata-Tago; Yusuke Ainoda; Takahiro Fujita; Ken Kikuchi (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Edwardsiella tarda bacteremia (ETB) can be a fatal disease in humans.